The Civil Wars - Two Views - Dubay, Robert (Teaching History: A Journal of Methods, 1991)
This videocassette is intended for use by students in grades seven through twelve. Besides the seventy-five minute tape, the purchase package contains numerous teacher assistance materials such as a text transcription, sample test questions, bibliographical guides, and a creative simulation exercise section.